DEVELOPMENT MODEL OF SOCIAL MEDIA MARKETING – CONSUMER LOYALTY MEDIATED BY BRAND EQUITY AND CONSUMER RESPONSE TO FASHION BRANDED PRODUCTS - Octavia, Ade; Hasbullah, Husni; Sriayudha, Yayuk (Dinasti International Journal of Digital Business Management, 2020)
Cunsumer loyalty is determined by a positive response to the perceived experience. The use of social media in marketing products can improve the quality of marketing. The purposes of this research are to: (1). Explain the relationship between social media marketing and consumer loyalty with brand equity as a mediation variable. (2). Explain the relationship between social media marketing and consumer loyalty with consumer response as a mediation variable (3). Develop a model of social media marketing and consumer loyalty relationships. The design of the research was done quantitatively to analyze the model of the relationship between social media marketing and consumer loyalty. To interpret quantitative results used focus Group discusion (FGD) methods and literature studies. The research sample numbered 200 respondents with consumer criteria of users of branded fashion products. Analysis tools using SEM with PLS Software. The results showed a positive and significant relationship between social media marketing to the consumer loyalty of fashion products both before and after mediated by brand equity and consumer response. The priority of the research to be conducted lies in how digital development in marketing contributes thought to the business world, government and how this study strengthens the theory for similar research